Internalisation of Presean Values in Social Learning to Strengthen Pancasila Ideology - Galih Suryadmaja; Christofer Satria; Dewi Puspita Ningsih; Retno Utari (Pancasila: Jurnal Keindonesiaan, 2025)
This research is motivated by the challenges of internalizing Pancasila values among sociology education students through an approach relevant to the local cultural context. One potential medium is the values of Presean culture, which can enrich the teaching of Pancasila ideology. The purpose of this study is to analyse the role of Presean cultural values in social learning and their contribution to strengthening students’ understanding of Pancasila. The study employed a qualitative approach with 15 participants consisting of sociology education students, lecturers, and local cultural figures. Data were collected through interviews, observations, and document analysis, then examined using a descriptive-interpretative method. The findings reveal that the internalisation of Presean values-such as courage, sportsmanship, and adherence to rules-positively enhances students’ comprehension of Pancasila principles. In addition, this culturally based learning increases students’ awareness of unity, social justice, and respect for human rights. These results suggest that integrating Presean cultural values into social education can serve as an effective alternative for strengthening Pancasila ideology among the younger generation.